Plexiform neurofibroma: shedding light on the investigational agents in clinical trials. (2nd January 2022) - Acar, Simge; Armstrong, Amy E.; Hirbe, Angela C.
ABSTRACT: Introduction: Neurofibromatosis Type 1 (NF1) is an autosomal dominant genetic condition, which predisposes individuals to the development of plexiform neurofibromas (PN), benign nerve sheath tumors seen in 30–50% of patients with NF1. These tumors may cause significant pain and disfigurement or may compromise organ function. Given the morbidity associated with these tumors, therapeutic options for patients with NF1-related PN are necessary. Areas covered: We searched the www.clinicaltrials.gov database for 'plexiform neurofibroma.' This article summarizes completed and ongoing trials involving systemic therapies for PN. Expert opinion: Surgery is the mainstay treatment; however, complete resection is not possible in many cases. Numerous systemic therapies have been evaluated in patients with NF1, with MEK inhibitors (MEKi) showing the greatest efficacy for volumetric reduction and improvement in functional and patient-reported outcomes. The MEKi selumetinib is now FDA approved for the treatment of inoperable, symptomatic PN in pediatric NF1 patients. Questions remain regarding the use of this drug class in terms of when to initiate therapy, overall duration, reduced dosing schedules, and side effect management. Future studies are needed to fully understand the clinical application of MEKi and to evaluate other potential therapies through appropriate trial designs for this potentially devastating, manifestation in NF1.